2006
DOI: 10.1371/journal.pbio.0040204
|View full text |Cite
|
Sign up to set email alerts
|

DNA Detection Using Recombination Proteins

Abstract: DNA amplification is essential to most nucleic acid testing strategies, but established techniques require sophisticated equipment or complex experimental procedures, and their uptake outside specialised laboratories has been limited. Our novel approach, recombinase polymerase amplification (RPA), couples isothermal recombinase-driven primer targeting of template material with strand-displacement DNA synthesis. It achieves exponential amplification with no need for pretreatment of sample DNA. Reactions are sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1,634
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,894 publications
(1,652 citation statements)
references
References 11 publications
4
1,634
0
14
Order By: Relevance
“…3 Recombinase polymerase amplification (RPA) offers significant advantages over other isothermal amplification techniques for point-of-care applications: it requires a lower amplification temperature, is tolerant to impure samples, amplifies targets to detectable levels within minutes, and uses lyophilized enzymes to enable storage and transport at room temperature. 4,5 For these reasons, a number of recent reports have proposed RPA-based strategies for the detection of pathogens. [6][7][8][9][10] Although some papers demonstrate a relationship between nucleic acid concentration and onset of amplification, 10,11 to the best of our knowledge, RPA has not yet been implemented to quantify sample concentration using a standard curve.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recombinase polymerase amplification (RPA) offers significant advantages over other isothermal amplification techniques for point-of-care applications: it requires a lower amplification temperature, is tolerant to impure samples, amplifies targets to detectable levels within minutes, and uses lyophilized enzymes to enable storage and transport at room temperature. 4,5 For these reasons, a number of recent reports have proposed RPA-based strategies for the detection of pathogens. [6][7][8][9][10] Although some papers demonstrate a relationship between nucleic acid concentration and onset of amplification, 10,11 to the best of our knowledge, RPA has not yet been implemented to quantify sample concentration using a standard curve.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a prototype reverse transcription-recombinase polymerase amplification (RT-RPA) assay that is quick and can be undertaken in low resource settings [15]. The RPA is an isothermal nucleic acid amplification technology where reactions take place at a low and constant temperature between 22°C and 45°C [16]. Fluorescence was detected using a portable real-time fluorometer, ‘Twista®’, which has a small footprint and can be rendered entirely portable with the addition of a rechargeable battery pack, developed by the private sector collaborator, TwistDx.…”
Section: Specific Objectivesmentioning
confidence: 99%
“…Shin et al [69] have demonstrated one of the most sophisticated and sensitive approaches for isothermal PCR-like amplification of ds-DNA using a solid-phase immobilized primer. This was carried out using recombinase polymerase amplification (RPA) [70,71] which employs a uvsX recombinase enzyme of specific activity isolated from T4 phage. In this case the enzyme is intended to "substitute" the thermal denaturation step normally performed during PCR amplification.…”
Section: Isothermal Amplification On Microarraysmentioning
confidence: 99%